2022
DOI: 10.3389/fimmu.2022.932181
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Gender Differences and Clinical Outcome in Patients With the Antiphospholipid Syndrome

Abstract: Antiphospholipid syndrome (APS), characterized by artherial and/or venous thrombosis, pregnancy morbidity and “antiphospholipid” antibodies (aPLs), is more common in women than in men, with a female to male ratio of about 3.5:1. Only few studies have investigated the clinical differences between male and female patients with APS. Therefore, this study was aimed to analyze the differences of clinical manifestations and laboratory tests, at diagnosis, between female and male APS patients and the clinical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, when describing only PAPS, the female-to-male ratio decreases or is even inverted. 3,26 Since thrombotic events are easier to assess and register than aPL positivity in the healthy population, more accurate data are available on APS.…”
Section: Thrombosis In Apl Carriers and Aps Patients Incidence And Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, when describing only PAPS, the female-to-male ratio decreases or is even inverted. 3,26 Since thrombotic events are easier to assess and register than aPL positivity in the healthy population, more accurate data are available on APS.…”
Section: Thrombosis In Apl Carriers and Aps Patients Incidence And Pr...mentioning
confidence: 99%
“…In spite of females making up the majority of APS patients (mostly due to its association with SLE and obstetric events), male patients have an increased risk of thrombosis and thrombosis recurrence compared to females in most studies. 26,54,55 Age Some studies, including a systematic review of 43 studies with stroke related to APS, showed that aPL may have a big role in strokes in younger patients. Individuals younger than 50 years and positive aPL have an increased risk for thrombotic cerebrovascular events by almost sixfold compared to those younger than 50 years and negative aPL.…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…When conditions such as SLE and obstetric APS are removed, the ratio of APS in women and men has been reported to be between 2–5:1 6 . APS in men is more commonly primary (6:1), whereas in women secondary APS is more common (1.4:1) 7 …”
Section: Gender and Apsmentioning
confidence: 99%
“…6 APS in men is more commonly primary (6:1), whereas in women secondary APS is more common (1.4:1). 7 Although peripheral thrombosis and pulmonary embolus are the most common APS manifestations in both sexes, the distribution of thrombosis varies. Male PAPS patients present more frequently with myocardial infarction, mesenteric and hepatic vein thrombosis whereas more female PAPS patients have strokes, 6 livedo and headaches.…”
Section: Gender and Apsmentioning
confidence: 99%